2022
DOI: 10.1002/pits.22666
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' and teachers' experience of school re‐entry after a child's prolonged absence due to severe illness

Abstract: School re‐entry of children who have been absent from school due to severe illness is a complex process and requires effort and adjustment from the child and his parents, teachers, school systems, and classmates. To contribute to the understanding and accuracy of the school re‐entry process of ill children, and to the development of re‐entry programs in Israel, the present study examined the re‐entry experience from the viewpoint of mothers and teachers. The study included 27 semi‐structured interviews with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 34 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…There was a range of both negative and positive experiences with parent–school faculty communication. Parents who described negative experiences felt burdened with the responsibility of monitoring their child’s progress [ 11 ], reminding school faculty of their child’s needs [ 21 , 38 , 19 ], and taking the initiative to educate school faculty on their child’s illness [ 24 ]. Across studies, parents reported that teachers needed frequent reminders regarding their child’s needs and ongoing communication to get the appropriate support in place for their child [ 11 , 21 , 38 , 19 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There was a range of both negative and positive experiences with parent–school faculty communication. Parents who described negative experiences felt burdened with the responsibility of monitoring their child’s progress [ 11 ], reminding school faculty of their child’s needs [ 21 , 38 , 19 ], and taking the initiative to educate school faculty on their child’s illness [ 24 ]. Across studies, parents reported that teachers needed frequent reminders regarding their child’s needs and ongoing communication to get the appropriate support in place for their child [ 11 , 21 , 38 , 19 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that parents felt educational support offered was school dependent [ 48 ]. Parents expressed the desire for a standardized approach to supporting families during integration across schools, such as a protocol or liaison [ 24 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations